"Ei Lacerda! Seu governo é uma #%$&*!": repertórios de ação coletiva e performance na dinâmica de afirmação pública do Movimento Fora Lacerda - Ana Claudia de Souza Inez (2016)
The research envisions the dynamics of mobilization of Movimento Føra Lacerda, formed in 2011 from an aggregation of publics and social actors with common causes and interests regarding the controversial actions of Prefeitura Municipal de Belo Horizonte, during the first mandate of Márcio Lacerda from Partido Socialist Brasileiro (PSB). The study develops a theoretical path that discuss the emerging concept of public, the tactical perspective of the repertoires of collective action and the performative dimension of public statement. After that, we present an analysis of the way that this mobilized public manifests and poses itself publicly during the three marches organized by its members between 2011 and 2012, from six elements of performance. Thus, we intend to understand how this aggregation of subjects affected by the municipal administration publicly postulates their claims when organizing events permeated by a performative dimension. Therefore, proposes to analyze the communicative actions for social mobilization of MFL in a tactical perspective , trying to see evidence of your planning and your drive in an attempt to gain more visibility, legitimacy and influence.